HUBUNGAN METODE QUDWAH (KETELADANAN) DENGAN PEMBENTUKAN KARAKTER SISWA PADA PEMBELAJARAN PAI DI SMP N 7 BUKITTINGGI - Sadri , Milda; Supriadi, Supriadi; Januar, Januar; Khairuddin, Khairuddin (CV. ADIBA AISHA AMIRA, 2024)
The research is prompted by a number of issues that have been seen, including the persistence of issues with lost property, peer bullying, and the use of derogatory language by students. The goal of this study was to ascertain the significance of the connection between SMP N 7 Bukittinggi's Qudwah technique (exemplary) and the development of student character. This study is a quantitative correlational study. For this investigation, a sample of up to 35 students was selected using proportionate random sampling. The research tool in this study was a questionnaire. The Pearson Product Moment Hypothesis Test with sig. (2-tailed) 0.877 and greater than 0.05, where Ha is rejected and H0 is accepted, is used in the analysis findings technique. Therefore, it can be said that there is very low relationship.